EVALUASI TATA KELOLA TEKNOLOGI INFORMASI DENGAN FRAMWORK COBIT. 5 DI KEMENTERIAN ESDM - Abdul Hakim; Hoga Saragih; Agus Suharto (Jurnal Sistem Informasi, 2014)
This evaluation study discusses how information technology governance in the Ministry of Energy and Mineral Resources, conducted by the Center for Data and Information Technology ESDM as a NOC, which aims to determine the extent to which the management and use of IT in improving IT services in KESDM and recommend management policy proposals effective and efficient IT using COBIT 5 models. The data was collected by conducting interviews, questionnaires and observation. The results were adjusted to the data management domain COBIT 5 will be the capability of inter-domain evaluat assessment, judging from some of the values are the average of the current capability level 4 in the range of 0. The highest value of the capabilities found in APO, DSS and MEA that is equal to 4, while lowest value contained in the EDM by 2.